Textbook Analysis of "Sahabatku Indonesia BIPA 7” Level C1 Using BSNP Standards and Cunningsworth’s Theory - Annur, Yusri Fajri; Syafryadin, Syafryadin (Lingual Journal of Language and Culture, 2025)
This study examines the BIPA (Bahasa Indonesia bagi Penutur Asing) Textbook entitle "Sahabatku Indonesia BIPA 7" at the C1 level through the lens of the BSNP (Badan Standar Nasional Pendidikan) standards and Cunningsworth's Theory of textbook evaluation. The purpose of this analysis is to assess the alignment of the textbook with established Indonesian educational standards for foreign language learners and to evaluate its pedagogical soundness. The study employs qualitative methods, involving a detailed content analysis of the textbook, comparing its structure and materials to the BSNP's criteria for educational resources, such as content accuracy, language proficiency progression, and cultural integration. Additionally, Cunningsworth’s framework is used to analyze the appropriateness of the textbook’s design, including its educational goals, content relevance, and learner engagement. The results show that the "Sahabatku Indonesia BIPA 7" textbook generally meets the BSNP standards, though there are areas for improvement in terms of cultural sensitivity and learner-centered activities. The findings suggest that while the textbook supports the development of both language and cultural understanding, further refinement could enhance its effectiveness as a comprehensive teaching tool. This analysis contributes to the field of Indonesian language teaching by providing insights into textbook evaluation and offers recommendations for future revisions to align with best practices in language education.